New Chummidae (Araneae): quadrupling the size of the clade - Jocqué, Rudy; Alderweireldt, Mark (European Journal of Taxonomy, 2018)
The recently described family Chummidae, now the sister clade of Macrobuninae, so far only known from two South African species, is extended with seven new species, six from the southern part of South Africa and one from Lesotho: Chumma bicolor sp. nov. (♀), C. foliata sp. nov. (♂♀), C. interfluvialis sp. nov. (♂♀), C. lesotho sp. nov. (♀), C. striata sp. nov. (♂♀), C. subridens sp. nov. (♂♀) and C. tsitsikamma sp. nov. ♂. A key to the species is provided. Although Chumma is part of a clade containing the Macrobuninae, it is argued that the family name Chummidae should remain valid.